Effects of Different Substrate Ratios on the Growth and Physiology of Sequoia sempervirens Container Seedlings. Issue 3 (3rd July 2019) - Meng, Ge-Lei; Luan, Dong-Tao; Tai, Zhi-Juan; Deng, Ji-Feng; Han, Jian-Qiu; Zhou, Yu-Mei
Abstract: Container technology can effectively control soil environment and nutrient status to obtain the optimal plant growth condition. Peat, green waste compost (GWC), soil and perlite were used as substrate materials to study the effects of different substrate ratios on growth and physiology of 1.5-year-old Sequoia sempervirens container seedlings. The optimal substrate ratio of S. sempervirens container seedlings was obtained by L9 (3 4 ) orthogonal design and was finally evaluated by principal component analysis. The volume ratio of peat: GWC: soil: perlite of 4: 1.5: 1: 2 was the best substrate ratio for S. sempervirens across all parameters, whose porosity, bulk density (BD) and gas-water ratio (GWR) were within the ideal ranges. The concentrations of total nitrogen (TN) of 1.40% and total phosphorus (TP) of 0.13% were the highest among the nine different substrates. The total potassium (TK) and electrical conductivity (EC) were 0.13% and 0.70 ms cm −1, respectively. In addition, the plant height and ground diameter growing in the substrate were increased by 28% and 39% compared to their respective initial values. The content of peat and GCW had significant effects on growth ( p  < 0.01). The GWR in T2 (peat: GWC: soil: perlite = 6: 1: 0.5: 2) and T6 (peat: GWC: soil: perlite = 4: 0.5: 0.5: 1) are not suitable for S. sempervirens container seedlings. The PCA ranking of the 9 groups of substrates is: T8 > T1 > T4 > T3 > T2 > T5 > T7 > T9 > T6. The combination of peat, GWC, soil and perlite in an appropriate ratio could provide a good environment for S. sempervirens container seedlings.